KUALITAS BIOPLASTIK DARI UMBI SINGKONG KARET DENGAN PENAMBAHAN KOMBINASI PLASTICIZER GLISEROL DENGAN SORBITOL DAN KITOSAN - Asngad, Aminah; Marudin, Ervian Jan; Cahyo, Devi Setyaning (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
High plastic demand has the potential to cause problems because plastic is a synthetic polymer made from petroleum that is difficult to decipher. Therefore, saving the current development of biodegradable plastics that can be decomposed by microorganisms naturally. Cassava rubber tubers are rarely used because they contain HCN toxin but have a carbohydrate content of 98.4674%, so it has the potential as a bio-plastic material. The purpose of this study was to determine the Bioplastic Quality of Cassava Rubber with the addition of a combination of Plasticizer Glycerol with Sorbitol and Chitosan. The study was conducted in the lab. Biology FKIP UMS, research methods used are experimental research methods. The study design used was completely randomized design with 2 treatment factors, namely: treatment factor 1 volume of glycerol (G), G 1 = 3ml; G 2 = 5ml; G 3 = 7ml. Treatment factors are 2 types of Plasticizer (P), P1 = Sorbitol and; P2 = Chitosan. The analysis used is descriptive qualitative used to test tensile resistance, elongation at break. Based on the results of the study showed the strongest spacer resistance, G1P1 which is 17.20N / mm², and the highest breaking length, G3P1 which is 24.00%. with sorbitol and chitosan.